2017
DOI: 10.1177/1178224216684831
|View full text |Cite
|
Sign up to set email alerts
|

The Exercise of Autonomy by Older Cancer Patients in Palliative Care: The Biotechnoscientific and Biopolitical Paradigms and the Bioethics of Protection

Abstract: Toward the end of life, older cancer patients with terminal illness often prefer palliative over life-extending care and also prefer to die at home. However, care planning is not always consistent with patients’ preferences. In this article, discussions will be centered on patients’ autonomy of exercising control over their bodies within the current biotechnoscientific paradigm and in the context of population aging. More specifically, the biopolitical strategy of medicine in the context of hospital-centered h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 26 publications
0
15
0
4
Order By: Relevance
“…Increasing the focus on the process of selecting patients to different levels of treatment will be highly important, both for the individual patient and for the healthcare system. It is essential to perform geriatric assessments systematically in the preoperative work-up [ 43 45 ], pay attention to the concept of prehabilitation [ 46 ], and increase focus on patient preferences [ 47 ]. Recent reports have demonstrated the value of a geriatric assessment in summarizing the patient's degree of frailty and predicting postoperative morbidity and mortality for older patients with colon cancer [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the focus on the process of selecting patients to different levels of treatment will be highly important, both for the individual patient and for the healthcare system. It is essential to perform geriatric assessments systematically in the preoperative work-up [ 43 45 ], pay attention to the concept of prehabilitation [ 46 ], and increase focus on patient preferences [ 47 ]. Recent reports have demonstrated the value of a geriatric assessment in summarizing the patient's degree of frailty and predicting postoperative morbidity and mortality for older patients with colon cancer [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider that personal patient preferences regarding treatment decisions might vary substantially among older patients. In the late stages of life, some needs, like preserving the remaining quality of life, may outweigh the need for radical treatment [ 47 , 53 ]. It has been shown that the physician’s recommendation was the most decisive factor in influencing the patient’s decision [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Niemeyer-Guimara ˜es and Schramm [17] examined the increasing number of frail, older cancer patients who were admitted to ICUs. The article explored the importance of understanding to what extent patients are able to demonstrate control of their own bodies and wishes in terminal care.…”
Section: Communication At the End Of Lifementioning
confidence: 99%
“…It is important to consider that personal patient preferences regarding treatment decisions might vary substantially among older patients. In the late stages of life, some needs, like preserving the remaining quality of life, may outweigh the need for radical treatment [47,53]. It has been shown that the physician's recommendation was the most decisive factor in in uencing the patient's decision [54].…”
Section: All Patientsmentioning
confidence: 99%
“…Increasing the focus on the process of selecting patients to different levels of treatment will be highly important, both for the individual patient and for the healthcare system. It is essential to perform geriatric assessments systematically in the preoperative work-up [43][44][45], pay attention to the concept of prehabilitation [46], and increase focus on patient preferences [47]. Recent reports have demonstrated the value of a geriatric assessment in summarizing the patient's degree of frailty and predicting postoperative morbidity and mortality for older patients with colon cancer [48].…”
Section: All Patientsmentioning
confidence: 99%